Relation between emitted CO₂, asset expenditures, produced energy from renewables and energy consumption: Evidence from Bulgaria - Tsvetana Harizanova-Metodieva; Hristina Harizanova-Bartos (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The paper explores the relation between emitted CO2 in the atmosphere, asset expenditure, produced energy from renewables and energy consumption. ARDL model was developed on the basis of data for Bulgaria (2000 - 2018). As a whole the increase in asset expenditures leads to increase in emitted carbon dioxide in the short-run and in the long-run. The increase in the produced energy from renewables leads to decrease in the emitted carbon dioxide in a long-run, while in the short-run the relation is insignificant. In a short-run the energy consumption and emitted carbon dioxide are in a positive relation: the increase in energy consumption leads to increase in the emitted pollutant.
Keywords: C32; Q50; 330; ARDL model; emitted CO2; asset expenditures; produced energy from renewables; energy consumption